The effect of hypertension on renal functions in patients with acute coronary syndrome - Uyan, Umut (The European Research Journal, 2023)
Objectives: In patients with acute coronary syndrome, age, ejection fraction, diabetes, hypertension, and chronic kidney disease (CKD) are regarded as independent risk factors for the development of acute kidney disease (ACD). This research evaluated the glomerular filtration rates (GFR) of acute coronary syndrome patient groups who were hypertensive and those who were not. Methods: This retrospective analysis comprised 764 patients with acute coronary syndrome who had applied to our institution before coronary angiography. There were two groups created from these patients. In the first group, there were 383 hypertensive patients; in the second group, there were 381 non-hypertensive patients. To assess how well these patients' kidneys were functioning, GFR was determined and compared. Results: The mean age of the two groups did not significantly differ from one another (p = 0.053). The standard lipid measures of total cholesterol, triglyceride, low-density lipoprotein-cholesterol, and high-density lipoprotein-cholesterol levels did not differ substantially between the two groups. The two groups had no discernible difference regarding high-sensitivity C-reactive protein, N-terminal fragment brain natriuretic peptides, creatinine, and thrombocyte levels. Systolic and diastolic blood pressure, as well as diabetes mellitus, were all considerably higher in the hypertensive patients’ group (p < 0.001). The GFR in hypertensive patients was substantially lower (64.83 ± 19.76 vs. 70.71 ± 19.19, p < 0.001) Conclusions: Our research revealed a strong link between hypertension and diminished renal function. This leads us to believe that hypertension may be a separate risk factor for the decline in renal function in acute coronary syndrome patients.